Resenha de: The voyages of David de Vries - Rodrigues, Maria Regina da Cunha (Revista de História, 1969)
PARR (Charles McKew). — The Voyages of David de Vries. Navifator and Adventurer whose writings reveal why the Dutch lost America to the English. Thomas Y. Crowell Company. New York. 1969. 304 páginas e 24 ilustrações. US$ 8.95.